Інформаційний кіоск як новий інструмент у рекламній діяльності компанії - Вовк, Наталія; Гаргат, Олег; Керенович, Лілія (Видавництво Львівської політехніки, 2017)
This article highlights the advantages and the technical characteristics of an informational kiosk as a new promotional tool in the promotional activities of companies, particularly in the company's activities «Freshpr», to establish effective communication with customers and consumers.
Keywords: FreshPr; інформаційний кіоск; новий продукт; рекламна діяльність; технічні характеристики; клієнти; споживачі; «Народна аптека»; pr-діяльність